Performance and emissions of a diesel engine fuelled with ultrasonically produced tobacco seed oil methyl ester: An RSM optimization study - Binh Vu Duc; Van Vuong Nguyen; Du Nguyen; Thanh Hai Truong (Center of Biomass & Renewable Energy (CBIORE), 2026)
Biodiesel plays an important role in making diesel engines more environmentally friendly and sustainable. Biodiesel use can significantly lower emissions of harmful pollutants, contributing to cleaner air and a reduced impact on climate change. Although there is an increasing body of research on non-edible biodiesel feedstocks, few studies have been able to systematically correlate fuel production, blend variation, and engine load optimization with a single statistical framework. This study fills this gap by combining ultrasonic-assisted two-step transesterification of tobacco seed oil (TSO) with response surface methodology to determine engine performance and emissions. Acid esterification was performed to produce TSO methyl ester, which was subjected to transesterification with NaOH under ultrasonic irradiation, to guarantee efficient conversion and low levels of free fatty acids. Indeed, TSO biodiesel and diesel fuel blends were tested on the engine under different loads. The findings indicate that the engine has a critical operating point of Engine Load (EL) = 96.90% and Lower Heating Value (LHV) = 41.82 MJ/kg, at which the engine has a peak thermal performance with BTE = 32.98% and BSFC = 0.27 kg/kWh. This indicates a very effective conversion of energy because of high in-cylinder temperature and pressure. Additionally, CO and HC emissions are significantly reduced, meaning that the combustion is almost complete. Nevertheless, NOx emissions increase dramatically to 657.74 ppm, proving the thermal penalty of high-temperature operation. This trade-off is validated by multi-objective optimization, which offers a strong framework to balance efficiency and emissions in biodiesel-powered engines.